STUDY ON SYMBOLIC MEANING INTERACTION ON ETHNIC DIFFERENCE IN INTER-CULTURAL COMMUNICATION AMONG NEW SETTLER INHABITAT IN YOGYAKARTA - Sigit Tripambudi; Ida Wiendijarti (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2015)
Indonesia consist of many tribes which have variety of difference culture, Thus, Indonesian is usually called as multiethnic tribe. Badan Pusat Statistik (BPS) noticed Indonesia has 1128 tribes with 746 local dialects which spread in 13.000 islands from Sabang to Merauke in 2011. Yogyakarta is usually called as mini Indonesia. Various comers both domestic also foreigner go into Yogyakarta. Therefore, this observation would see how’s individual with variety of ethincal background and interaction experiences gave the meaning of ethnical difference. This research used Symbolic Interaction. Theory, Identity Theory, Social Identity Theory and Communication Theory of Identity. Present research establish with sets of interview and observation on newcomers in Yogyakarta those are Batak, Sunda, NTT, Papua and China ethnics. The result described that : Indentity based on tribes ethnic is the most powerfull indentity compared to identity based on another ethnic. Ethnic identity formed powerful in family and environment which is teach certain values. New comer ethnic identity in Yogyakarta is more powerful because they live in new comer communities in same ethnic. New comers in Yogyakarta got meaning ethnic difference dominantly, i.e. as nation uniqueness and properties which is differentiate Indonesian from others. However, this situation makes Indonesia troubled with inter-ethnic conflict. New comers in Yogyakarta which is came from various ethnic being felt discriminatively yet. They are new comers from ethnic which is extremely different from physical, instance: skin color, hair type and physical posture. No one of new comers in Yogyakarta which is relatively similar with most ethnic or tribe in Indonesia feels discriminative. New Comers in Yogyakarta appraise that majority domination ethnic is Javanese which is dominate in economy and administration aspect.